The magic school bus. Season three [videorecording (DVD)] - Tomlin, Lily; DeSanto, Daniel, 1980-; Luttrell, Erica, 1982- (Scholastic, 2015)
Ms. Frizzle and her class journey inside a beehive, take a trip to the arctic, and learn about electricity in these super fun classics.